Validation of Repeated Endothelial Function Measurements Using EndoPAT in Stroke - Hansen, Aina S.; Butt, Jawad H.; Holm-Yildiz, Sonja; Karlsson, William; Kruuse, Christina (Frontiers in Neurology, 2017)
Background: Decreased endothelial function (EF) may be a prognostic marker for stroke. Measuring pharmacological effects on EF may be of interest in the development of personalized medicine for stroke prevention. In this study, we assessed the reliability of repeated EF measurements using a pulse amplitude tonometry (PAT) technology in acute stroke patients. Similar, reliability was tested in healthy subjects devoid of vascular disease to estimate reactivity and reliability in a younger non-stroke population. Material and Methods: EF was assessed using the EndoPAT2000 in 20 healthy volunteers (men 50%, mean age 35.853.47 years) and 21 stroke patients (men 52%, mean age 66.382.85 years, mean NIHSS 4.09  0.53) under standardized conditions. EF was measured as the reactive hyperemia index (RHI), lnRHI and Framingham RHI (fRHI). Measurements were separated by 1.5 h and 24 h to assess same-day and day-to-day reliability, respectively. Results: Fair to moderate correlations of measurements (ICCsame-day 0.29 and ICCday-to-day 0.52) was detected in healthy subjects. In stroke patients we found moderate to substantial correlation of both same-day and day-to-day repeated measurements (ICCsame-day 0.40 and ICCday-to-day 0.62). fRHI compared with RHI and lnRHI showed best reliability. Conclusions: Repeated measurements of fRHI in stroke patients show moderate reliability on same-day and substantial on day-to-day measurements. Likewise, in healthy subjects there was substantial reliability on day-to-day measurement, but only moderate on same-day measurements. In general, day-to-day correlation of repeated EF measurements was far better than that of same-day measurements, which ranged from poor to moderate depending on the specific outcome measure of EF. A possible carry-over effect should be considered if same-day repeated testing of drug effects is applied in future studies.